Shoot transcriptome revealed widespread differential expression and potential molecular mechanisms of chickpea (Cicer arietinum L.) against Fusarium wilt - Bhutia, Karma L.; Ahmad, Mahtab; Kisku, Anima; Sudhan, R. A.; Bhutia, Nangsol D.; Sharma, V. K.; Prasad, Bishun Deo; Thudi, Mahendar; Obročník, Oliver; Bárek, Viliam; Brestic, Marian; Skalicky, Milan; et al. (Frontiers in Microbiology, 2024)
The yield of chickpea is severely hampered by infection wilt caused by several races of Fusarium oxysporum f. sp. ciceris (Foc). To understand the underlying molecular mechanisms of resistance against Foc4 Fusarium wilt, RNA sequencing-based shoot transcriptome data of two contrasting chickpea genotypes, namely KWR 108 (resistant) and GL 13001 (susceptible) were generated and analyzed. The shoot transcriptome data showed 1103 and 1221 significant DEGs in chickpea genotypes KWR 108 and GL 13001, respectively. Among these, 495 and 608 genes were significantly down and up-regulated in genotypes KWR 108, and 427 and 794 genes were significantly down and up-regulated in genotype GL 13001. The gene ontology (GO) analysis of significant DEGs was performed and the GO of the top 50 DEGs in two contrasting chickpea genotypes showed the highest cellular components as membrane and nucleus, and also molecular functions including nucleotide binding, metal ion binding, transferase, kinase, and oxidoreductase activity, etc., involved in biological processes such as phosphorylation, oxidation-reduction, cell redox homeostasis process and DNA repair, etc. Compared to the susceptible genotype which showed significant up-regulation of genes involved in processes like DNA repair, the significantly up-regulated DEGs of the resistant genotypes were involved in metabolisms like energy metabolism and environmental adaptation, particularly host-pathogen interaction. Indicates an efficient utilization of environmental adaptation pathways, energy homeostasis and stable DNA molecules as the strategy to cope with Fusarium wilt infection in chickpea. The findings of the study will be useful in targeting the genes in designing gene-based markers for association mapping with the traits of interest in chickpea under Fusarium wilt which could be efficiently utilized in marker-assisted breeding of chickpea, particularly against Foc4 Fusarium wilt.